Penelitian berpikir kritis calon guru pendidikan matematika Di Indonesia (2015-2023): Tinjauan bibliometrik - Siahaan, Erika Yohanna Seventina; Muhammad, Ilham; Dasari, Dadan; Maharani, Swasti (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2023)
Critical thinking involves being mentally organized and participating in a judgmental process to solve problems. The purpose of this study is to look at the focus of research related to critical thinking of pre-service teacher teachers of mathematics education, especially in Indonesia from 2015 to 2023. The method used in this study is a descriptive bibliometric analysis method. The Scopus database is used to obtain the necessary data. The results of the research show that publications related to the critical thinking of pre-service teacher teachers of mathematics education in Indonesia have increased from 2018 to 2020. Most of the publications were published in conference papers and some were in Q2 journals. The research focus is divided into 4 sections, namely, 1) mathematics teacher , mathematical problems , algebra , and qualitative research ; 2) critical thinking skills , mathematics education , and learning systems ; 3) problem based learning and STEM; 4) data analysis techniques, information analysis. The material that is the focus of research is algebra. New themes for this field are experimental research, digital platforms, quantitative methods, and group theory. The keywords of critical thinking skills are not directly connected with these new themes